Computational Insights into Leucaena leucocephala Extract Shampoo as a Malassezia furfur Anti-Dandruff Agent - Hibatulloh, Muhammad Farhan; Nafisa, Tsabita; Afnan, Muhammad Syifaul; Andriani, Made Prasanti; Widanto, Cika Abadi Laily; Wisudanti, Desie Dwi (Journal of Agromedicine and Medical Sciences, 2025)
Dandruff is a scalp condition characterized by excessive flaking resulting from colonization by the fungus Malassezia furfur. Chemical-based anti-dandruff shampoos frequently result in side effects, including irritation, resistance, and hair discoloration. This study investigates the efficacy of Leucaena leucocephala leaf extract as a natural treatment for dandruff using an in-silico methodology. This research employed molecular modeling and docking assays targeting the 14-alpha lanosterol demethylase enzyme (CYP51), the primary antifungal target in Malassezia furfur. The docking results indicated that the active compounds in Leucaena leucocephala leaves, namely squalene and lupeol, exhibit a competitive binding affinity for CYP51, similar to the mechanism of action of ketoconazole. Squalene engages in polar interactions akin to the natural ligands of CYP51, whereas lupeol demonstrates robust hydrophobic interactions, suggesting its potential as an enzyme inhibitor. The findings indicate that herbal compounds derived from Leucaena leucocephala may serve as a natural alternative for dandruff treatment, presenting a reduced risk of side effects relative to synthetic chemicals. Further in vivo studies are necessary to validate the effectiveness and safety of anti-dandruff topical formulations. Keywords: CYP51, Dandruff, Leucaena leucocephala, Malassezia furfur, Natural antifungal